2005
DOI: 10.1111/j.1742-4658.2005.04686.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate positioning by His92 is important in catalysis by purple acid phosphatase

Abstract: The binuclear metalloenzyme purple acid phosphatase (PAP) [1], which may be involved in disorders such as osteoporosis [2][3][4], Gaucher disease [5], hairy cell leukemia [6], and AIDS [7] is widely distributed in mammalian tissues [8,9]. The expression level of PAP [also referred to as tartrate resistant acid phosphatase (TRAP) or type 5 acid phosphatase (AcP5; EC 3.1.3.2)] is elevated in these disorders, suggesting a relationship between the increased levels of the enzyme and the clinical picture. The presum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…In agreement with previous studies [40,[45][46][47] pK es2 is assigned to a conserved histidine residue in the second coordination sphere, which is likely to act as a proton donor to the leaving alcohol group during catalysis [14,[47][48][49]. Site-directed mutagenesis studies identified His92 as the likely residue [47].…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with previous studies [40,[45][46][47] pK es2 is assigned to a conserved histidine residue in the second coordination sphere, which is likely to act as a proton donor to the leaving alcohol group during catalysis [14,[47][48][49]. Site-directed mutagenesis studies identified His92 as the likely residue [47].…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufsupporting
confidence: 89%
“…In comparison with the native Fe(III)Fe(II) form of Uf each pK a in the Fe(III)Ni(II) derivative is shifted towards more alkaline values, resulting in a corresponding shift of the pH for optimum reactivity from 5.0 to 5.5 upon replacing Fe(II) with Ni(II). Based on an inspection of the active site of the enzyme and previous studies [40,46,47], the following assignment is proposed:…”
Section: Kinetic Properties Of Fe(iii)ni(ii)-ufmentioning
confidence: 99%
“…21 For metallohydrolases, fluoride and vanadate are known inhibitors which have been shown to coordinate directly to the metal ion(s) in the active site and thus interfere with catalytic turnover. 1,20,[23][24][25][26][27][28] The two inhibitors are likely to affect different aspects of catalysis and hence may provide insight into different steps of the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…21 For metallohydrolases, fluoride and vanadate are known inhibitors which have been shown to coordinate directly to the metal ion(s) in the active site and thus interfere with catalytic turnover. 1,20,[23][24][25][26][27][28] The two inhibitors are likely to affect different aspects of catalysis and hence may provide insight into different steps of the reaction mechanism.The ability of fluoride to readily replace nucleophilic hydroxide groups can provide (i) an insight into the number of labile water/hydroxide binding sites in the active site, and (ii) the role of the terminally bound or bridging hydroxides in the reaction mechanism. 26,29 Fluoride, a well established osteogenic agent which promotes osteoblastic proliferation and differentiation at clinically relevant concentrations, inhibits animal PAPs in a pH-dependent manner.…”
mentioning
confidence: 99%
“…Thus, it will be important to take into account the role of this key residue in further development of predictive models of the specificity of UGT1A4, UGT1A3, and UGT1A1. Similarly, Funhoff et al (40) showed recently that a histidine residue plays an important role in positioning the substrate of the purple acid phosphatase, and Watts et al (41) identified a single active site histidine residue governing substrate selection of aromatic lyase family.…”
Section: Discussionmentioning
confidence: 95%